Analytical Hierarchy Process To Determine The Weights of Student Outcomes for Engineering Undergraduate Programs for ABET Accreditation - Nwafor, Chukwudi Thomas (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Engineering education is becoming more and more versatile and complex due to a number of courses offered by each engineering department. The criterion 4. a-k of the Accreditation Board for Engineering and Technology (ABET) consists of 2(two) class of interaction based on the program hard skills and soft skills which cover all the sets of programs. Analytical Hierarchy Process (AHP) is utilized for pair-wise comparison of the student’s outcomes in Engineering Undergraduate Programs of the whole world wide. In this study, it is attempted to estimate the realistic weights of the criterion 4 using the classical AHP, the weight of the Nine-Level Fundamental Scale of judgments are expressed via numerical scale order to represent the relative important among the multi-criteria decision making (MCDM) by collecting the responses from the diarchy which comprise of 4 affected parties (students, alumni, employees and academic staffs) at the various department of engineering from all parts of the world based on the outcome of the parties by means of survey questionnaires and internet website has been designed also to implement AHP judgments on the outcomes from the criterion 4a-k of the ABET. The focus of the data collection is to answer the question, “can the engineering undergraduate program demonstrate the level to which students have attained the anticipated student’s outcome?” The evidence of students learning is then used to identify student strengths and weakness related to each of the student outcome for making decision about how to improve the programs teaching and learning process, a defined weight calculated by applying classical AHP method. The implication of this research is that the faculty members can utilize the weights of the program outcomes generated as a result of this study and implement them for the continuous improvement process.

ÖZ: Mühendislik eğitimi her bir mühendislik bölümünde verilen derslerin sayısına bağlı olarak daha çeşitli ve karmaşık hale gelmektedir. Mühendislik ve Teknoloji Akreditasyon Kurulu’nun (MTAK) 4. kriteri (a-k) programın bileşenlerine göre (Tasarım, Bilim ve Matematik) tüm kümeleri aşağı yukarı kapsayan 2 (iki) sınıf içerir. Bu çalışmada, mühendislik lisans programlarının öğrenci çıktılarının çiftler halinde karşılaştırılması için Analitik Hiyerarşi Süreci (AHS) kullanılmıştır. Bu çalışmada, klasik AHP yöntemi kullanılarak 4. kriterin gerçekçi ağırlıklarının belirlenmesi amaçlanmıştır. Dünyadaki çeşitli mühendislik bölümlerinden dört gruba (öğrenci, mezun, iş veren ve akademisyen) öğrenci çıktılarının ağırlıklarını dokuz seviyede karşılaştırmaları için bir anket uygulanmıştır. Toplanan cevaplar çok kriterli karar verme çalışmalarının bir parşaçı olarak AHP yöntemiyle 4. kriterdeki öğrenci çıktılarının (a-k) göreli ağırlıklarının belirlenmesinde kullanılmıştır. Veri toplamanın odağı “mühendislik lisans programı öğrencilerinin öğrenci çıktılarına beklenen ulaşım seviyesini sağladığını gösterebilir mi?” sorusunun cevabını bulmaktır. Daha sonra, öğrencilerin her bir öğrenci çıktısıyla ilgili olarak güçlü ve zayıf yönleri ve klasik AHP ile bulunan ağırlıklar kullanılarak mühendislik bölümlerinin öğretme ve öğrenme süreçlerinin geliştirilmesiyle ilgili karar verilebilir. Fakülte üyeleri bu çalışmayla bulunan ağırlıkları sürekli gelişim süreçlerinde kullanabilirler.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2016. Supervisor: Assist. Prof. Dr. Hüseyin Güden.
Keywords: Industrial Engineering--Education--Accrediation; Analytic Hierarchy Process (AHP); student outcomes; multiple-criteria decision making (MCDM); ABET Accreditation; Industrial Engineering